General statistics - Chase, Warren; Bown, Fred. (New York : Wiley, 1997)
The book presents a first course in statistics appropriate for students in a wide variety of disciplines, the only prerequisite being a knowledge of high school algebra. This is to acquaint students with the basic idea of inferential and descriptive statistics. All technical terms are defined in easy -to- grasp language; definitions, important formula and summaries of statistical tests are set off in boxes for quick reference. Concepts are introduced and introduced and reinforced with examples and exercises from a wide range of fields, from sports to medicine. All chapters begin with an introduction and end with a summary of the important ideas of the chapter. As in the second edition of the book, most exercises on hypothesis testing do not specify whether the traditional approach(finding the crical region), or the P-value approach should be used.
Includes bibliographical references (3rd section, p. 65-66) and index.
opc 04/07/13; uaj 05/05/2015
Loans
Keywords: Statistics; General statistics